Illocutionary act between barista and customers in Starbucks coffee shop at Changi airport - Isbandi Isbandi; Nurma Dhona Handayani (Journal of Research on English and Language Learning (J-REaLL), 2020)
This research primarily aimed to analyse the types of the illocutionary act proposed by Searle (1979), secondly to find the dominant type produced by both sides, between barista and customers' utterances at Starbucks coffeeshop Changi Airport. This research applied observational method and non-participatory technique as the way collecting the data. The design of this research were qualitative and quantitative research. Qualitative research is applied to analyse the data in the form text. In contrast, quantitative research used to count the number of utterances, to conclude which types of illocutionary acts find dominantly during the conversation. It was found that directive, representative, and expressive types were in the utterances. Meanwhile, commissive and declaration type did not find in the utterances. The result from this study showed that directives illocutionary act as the most frequently found in utterances, because the communication which takes place in coffeeshop between the baristas and customers usually only needed to ordering and just give information (informing).